Study Of Generalization of Fuzzy Closed Sets (International Journal of Scientific Research in Science and Technology, 2024)
In this present paper, we consider to investigate the concepts in fuzzy topological spaces, a brief survey of relevant basic concepts and results of generalization of fuzzy closed sets. The concept of fuzzy set was first introduced by Lotfi Zadeh in 1965. After the discovery of Fuzzy set by Zadeh, thoughts of the Fuzzy topology have been discussed by Chang who introduced the concept of fuzzy topological spaces as an extension to classical topological spaces. After that many authors studied topological properties under fuzzy settings and suggested different definitions for the same property which leads to different approaches. Also, some of the properties, theorems of the fuzzy topological space are not same as classical topological does. Fuzzy topology, fuzzy interior, fuzzy closure, fuzzy point, and fuzzy boundary are some basic concepts which play an important role in fuzzy topology.